Optical spectroscopy of Galactic field classical Be stars. Issue 3 (10th November 2020) - Banerjee, Gourav; Mathew, Blesson; Paul, K T; Subramaniam, Annapurni; Bhattacharyya, Suman; Anusha, R
ABSTRACT: In this study, we analyse the emission lines of different species present in 118 Galactic field classical Be stars in the wavelength range of 3800–9000 Å. We re-estimated the extinction parameter (A V ) for our sample stars using the newly available data from Gaia DR2 and suggest that it is important to consider A V while measuring the Balmer decrement (i.e. D 34 and D 54 ) values in classical Be stars. Subsequently, we estimated the Balmer decrement values for 105 program stars and found that ≈20 per cent of them show D 34 ≥ 2.7, implying that their circumstellar disc are generally optically thick in nature. One program star, HD 60855 shows H α in absorption – indicative of disc-less phase. From our analysis, we found that in classical Be stars, H α emission equivalent width values are mostly lower than 40 Å, which agrees with that present in literature. Moreover, we noticed that a threshold value of ∼10 Å of H α emission equivalent width is necessary for Fe ii emission to become visible. We also observed that emission line equivalent widths of H α, P14, Fe ii 5169, and O i 8446 Å for our program stars tend to be more intense in earlier spectral types, peaking mostly near B1-B2. Furthermore, we explored various formation regions of Ca ii emission lines around the circumstellar disc of classical Be stars. We suggest the possibility that Ca ii triplet emission can originate either in the circumbinary disc or from the cooler outer regions of the disc, which might not be isothermal in nature.